Paleoseismological evidence of multiple, large-magnitude earthquake surface ruptures on the active Mt. Morrone normal fault, central Apennines, Italy - I. Puliti; A. Pizzi; S. Gori; E. Falcucci; F. Galadini; M. Moro; M. Saroli; M. Saroli (Solid Earth)
The active Mt. Morrone Fault (MMF) and the related Sulmona intermountain basin constitute one of the most characteristic examples of the extensional tectonic landscape carving the central Apennines (Italy). Above the ∼ 22 km MMF, thousands of inhabitants concentrate on a thriving reality and a historical and cultural heritage of great significance. According to current knowledge, the last activation event of the whole MMF occurred ∼ 2000 years ago, and the maximum expected magnitude is M 6.6–7.0. Thus, the MMF today constitutes one of the most problematic structures in the central Apennines seismotectonic setting in terms of large-magnitude earthquake probability. Despite this, information on the activity of the MMF is presently relatively sparse, both for associated historical seismicity and paleoseismological data. To strengthen these knowledge weaknesses, we performed new extensive paleoseismological analyses (employing four trenches) in the central sector of the fault. Our goal was to supplement the limited existing dataset, constituted by a single paleoseismological study close to the northwestern tip of the fault. Additionally, we aimed to incorporate findings from a pair of studies focused on archaeoseismological and speleoseismological secondary evidence. Through these analyses, we unveiled four significant surface rupture events of the MMF, three of which occurred over the past 6000 years BP. Specifically, the youngest identified event occurred after 3.6–3.5 kyr BP, thus being chronologically consistent with the event in the second century CE, a penultimate event after 4.4 kyr BP, a previous event that occurred after 5.4–5.3 kyr BP, and the oldest event that took place after 9–8.9 kyr and (presumably) before 5.8–5.7 kyr BP. Considering that the estimated cumulative minimum vertical displacement encompassing the last three events is ∼ 140 cm, and based on the length of the fault at the surface, we can confirm that earthquakes with M 6.6–7.0 may be expected from the activation of the MMF with an inferred average recurrence interval not longer than 1800 years over the last ∼ 5.4 kyr.